Microdeletions in FMR2 may be a significant cause of premature ovarian failure. Issue 10 (1st October 1999) - Murray, Anna; Webb, James; Dennis, Nick; Conway, Gerard; Morton, Newton
Abstract : Genetic causes of premature ovarian failure (POF) include X chromosome deletions and fragile X (FRAXA) premutations. While screening a cohort of women with POF for FRAXA premutations, a more distal trinucleotide repeat, FRAXE, was also tested. We found an unexpected excess of FRAXE alleles with apparently fewer than 11 repeats in the POF group. However, sequence analysis of these alleles showed that the excess was caused by three females who carry cryptic deletions in FMR2, the gene associated with FRAXE. We propose that microdeletions within FMR2 may be a significant cause of premature ovarian failure, being found in 1.5% of women with the condition, and in only 0.04% of the general female population. The deletions may affect transcription of either FMR2 or an adjacent gene.